Peran Media Sosial TikTok dalam Pemasaran Pariwisata di Indonesia - Muhammad Afif Tarji; Rahmat Yumirwan Wiharjo (Jurnal Penelitian Ilmu Pariwisata, 2025)
Marketing has been widely used as a method for making effective, efficient and planned decisions in the business world. So many companies and institutions make various efforts to meet market demand with various marketing methods, one of which is through digital marketing. And this is none other than to maximize income and maximum profit. Many things are done, one example is choosing the right, efficient and up-to-date marketing method or strategy. Marketing through social media has recently been widely used by all groups, especially millennials in Indonesian tourism marketing activities. Not a few tourism actors try to promote their products or tourist destinations appropriately, efficiently and accurately to achieve targets through various platforms on social media. This article discusses a review of marketing through Tiktok for Indonesian tourist destinations. Articles taken from sources in the form of national journals, international journals and conference proceedings. Furthermore, the author will explain the taxonomy and summary of the review results. In the end, the author presents research opportunities that have the potential to be studied in the future.